Young rural women participation in the e-wallet programme and usage intensity of modern agricultural inputs in Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2018)
We assess the extent young rural women (YRW) participate in the federal government (FGN)e- wallet programme and the subsequent impact on usage intensity of modern agricultural inputs in Nigeria. Six hundred YRW were sampled across six geopolitical zones of Nigeria. Using double- hurdle, results show that YRW rarely participate in the e-wallet programme due to the cultural and traditional context which is anchored in beliefs, norms and practices that breed discrimination and feminized poverty. This implies that Nigeria's agricultural transformation agenda would only succeed if the FGN is able to draw on all its resources and talents, and if the YRW can be able to participate fully in the e-wallet programme. This will require intensified efforts to eliminate discrimination and promote equalities. To bridge the gender gap, the federal ministry of agriculture and rural development should pay close attention to the extent the participation of unmarried girls and young women, including nursing mothers in the e-wallet programme, may be limited by the cultural and/or domestic and child care duties. The findings suggest that FGN should discourage gender disparities in unequal access to agricultural inputs and pervasive, inequality, especially over ownership of agricultural land that limit women's contribution to household food baskets.
Keywords: J43; O40; O55; Q10; 330; Gender; e-wallet programme; modern agricultural inputs; young rural women; double-hurdle model; Nigeria